Global Exponential Robust Stability of Static Interval Neural Networks with Time Delay in the Leakage Term - Guiying Chen; Linshan Wang (Journal of Applied Mathematics)
The stability of a class of static interval neural networks with time delay in the leakage term is investigated. By using the method of M-matrix and the technique of delay differential inequality, we obtain some sufficient conditions ensuring the global exponential robust stability of the networks. The results in this paper extend the corresponding conclusions without leakage delay. An example is given to illustrate the effectiveness of the obtained results.